STRUCTURAL AND STYLISTIC FEATURES OF URAN AKATAYULY'S KUYS (EXAMPLES FROM "MEREKE", "SANLAQ", AND "QANAT QAQTI") - Saida Yelemanova; Lazat Akikhat (Arts Academy)
The proposed article is dedicated to the creative path of the kuyshi from the Tarbagatai region (PRC) — Uran Akatayuly. It is well known that Kazakh kuy art, depending on its geographical and regional characteristics as well as performance features, is divided into various regional kuy traditions. Among them, the kuy tradition of Eastern Kazakhstan has deep historical roots and covers a vast territory. One of its branches is the kuy school (күй мектебі) of the Kazakhs of the Xinjiang Uygur Autonomous Region of the People's Republic of China. In this region — in the Ili Kazakh Autonomous Prefecture, as well as in Altay, Tarbagatai, Ili, and the prefectures of Sanji, Boro-Tala, the Kumul region, Gansu province, and the cities of Kuytun, Shihezi, and Urumqi — about two million of our compatriots reside. The study of kuy art in these regions can be said to be at an early stage in domestic scholarship. The article addresses the following issues: 1) a description of the kuyshi’s creative work, and 2) a musical analysis of the most notable compositions by the above-mentioned performer. The article is based on materials collected during the author’s ethnographic and folklore expedition conducted in January 2024 in the Ili Kazakh Autonomous Prefecture (city of Kuldzha). The applied methods include the comparative-typological and system-ethnophonic approach (I. Matsiyevsky). The methodology for analyzing dombra kuys developed by Professor S. Öteğalieva is also used. For certain compositions, their origin stories and content are presented, along with a detailed musical analysis.